PENGARUH PEMBERIAN VARIASI PAKAN FERMENTASI TERHADAP PERTUMBUHAN DAN KEPADATAN ROTIFERA (Brachionus plicatilis ) UNTUK PAKAN NENER IKAN BANDENG (Chanos chanos) - Mohamad Mediko; Ni Wayan Sudatri; Deny Suhernawan Yusup (SIMBIOSIS, 2025)
Brachionus plicatilis is one of the zooplankton that is needed as food for fish larvae. So it is expected that the use of this alternative feed can help hatchery farmers to increase Rotifera production and increase the production of high quality nener. The objectives of the study were to determine the growth of Rotifera in cultures given variations of 4 additional feed ingredients fermented from chicken feces, wheat bran, rice bran and corn bran and to determine the growth response of milkfish (Chanos chanos) seeds fed with Rotifera from the best culture. The additional feed treatment given consisted of 5 factors (4 treatments and 1 control) fermented dried chicken feces, wheat bran, corn bran and rice bran, while the control was phytoplanton from UD Chlorella culture. The fermentation material used was EM4 (Efective Microorganisms 4 from Pt. Songgolangit Persada) The design used was a Randomized Group Design (RAK) with 4 replicate cultures. Giving variations of 4 feed ingredients that have been fermented affects the growth of Rotifera cultures. Growth can be seen from the density of each variation of 4 fermented ingredients namely wheat bran 276,750, corn bran 422,050, rice bran 567,650, chicken feces 169,450, Phytoplankton 77,300. Giving Rotifera cultured with rice bran to the growth of milkfish larvae influenced their growth. Milkfish larvae can grow after being given fermented Rotifera, but the SR value is very low. Milkfish larvae fed with fermented Rotifera had a low SR value of 32,73% mortality rate of 1,373 of 4,500 fish, compared to the SR value of Phytoplanton which was high at 78,15% mortality rate of 3,517 of 4,500 fish. Keywords: Cultivation, Bran, Feces, Culture, Rotifera